Upaya Meningkatkan Minat Belajar dan Hasil Belajar Melalui Penggunaan E-Modul Interaktif pada Peserta Didik Kelas VIII.6 SMP Negeri 2 Sungguminasa - Qanitah Bintu Kasman; Mutmainnah; Nurfadila Islami; Ramlawati; Sitti Saenab; Nur Janna (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to increase learning interest and cognitive learning outcomes on Earth's Structure and Its Development topics among eighth-grade students through the implementation of an interactive e-modul. This Classroom Action Research (CAR) followed the Kemmis and McTaggart framework, which spans two cycles, consisting of planning, action, observation, and reflection. The subjects of this study were 38 eighth-grade students. Data were collected using learning interest questionnaires and objective cognitive tests, then analyzed using descriptive quantitative statistics. The results revealed a continuous improvement across all stages. The initial baseline (pre-cycle) indicated low learning interest (48.50%) and extremely low cognitive achievement (mean score: 22.10, classical completeness: 10.5%). Following the introduction of the interactive e-modul in Cycle I, learning interest rose to 69.42% (High category), while the learning outcome mean slightly increased to 35.15 (classical completeness: 26.3%) due to technical adjustments. After optimizing group guidance and user navigation in Cycle II, student interest strengthened to 76.04%, and learning outcomes surged to a mean of 81.25, achieving a classical completeness of 84.2%. These findings confirm that the integration of interactive e-modules successfully fosters student engagement, reduces abstraction in science materials, and significantly enhances both students' learning interest and academic performance.